Die behauptete und die gelebte Migrationskrise: der widersprüchliche Fall Italien - Felicitas Hillmann (Geographica Helvetica, 2019)
Italy, situated prominently middle of the Mediterranean Sea, has been confronted with migration and refugee issues for a long time. Within the European migration system it is a telling example of the way the issue of migration is dealt with more generally. After a prolonged phase of ignoring the existing exigencies of integration and regulation of the already present migrants on the territory, the country experienced a peak of arrivals of migrants on its coastlines in 2015/16. Since then, numbers of in-migration have been decreasing. Still, in the public discourse the idea of an invasion, e.g. mass immigration, continues. For many years the SPRAR system had contributed to tackling a situation of crisis by involving civil society and by reaching out for solutions beyond management. The article emphasizes that the migration crisis can be understood only when taking into account different realities and expectations. It further presents the case study of Genoa. Here, the crisis is mastered by normalisation and local action.
Keywords: 710